New insights on the systematics of echinoids belonging to the family Spatangidae Gray, 1825 using a combined approach based on morphology, morphometry, and genetics - Stara, Paolo; Melis, Riccardo; Bellodi, Andrea; Follesa, Maria Cristina; Corradini, Carlo; Carugati, Laura; Mulas, Antonello; Sibiriu, Michela; Cannas, Rita (Frontiers in Marine Science, 2023)
Spatangoids are probably the least resolved group within echinoids, with known topological incongruencies between phylogenies derived from molecular (very scarce) and morphological data. The present work, based on the analysis of 270 specimens of Spatangidae (Echinoidea, Spatangoida) trawled in the Sardinian seas (Western Mediterranean), allowed us to verify the constancy of some characters that we consider to be diagnostic at the genus level —such as the path of the subanal fasciole and the relationship between labrum and adjacent ambulacral plates —and to distinguish two distinct forms within the studied material. Based on morphological characters, morphometrics, and molecular analyses (sequencing of two mitochondrial markers: cytochrome c oxidase subunit1 (COI) and 16S), most of the individuals were classified as morphotype A and attributed to the species Spatangus purpureus, the most common spatangoid in the Mediterranean Sea, while a few corresponded to a different morphotype (B), genetically close to the species Spatangus raschi. Preliminary morphological analyses seemed to indicate that morphotype B specimens from Sardinia are slightly different from S. raschi and from Spatangus subinermis individuals, the second species of the family known to occur in the Mediterranean Sea. On the basis of morpho-structural observations and molecular analyses, comparing Mediterranean living forms with species from other areas (Central Eastern Atlantic, North Sea and neighboring basins, South African Sea, Philippines and Indonesian Archipelago, New Zealand, and Hawaiian Islands), the clear distinction of S. purpureus from several other species classified as Spatangus was confirmed. Based on the morphological and genetic differences, we propose to maintain the genus Spatangus including in it only the type species S. purpureus among the living species and to establish the new genus Propespatagus nov. gen. to include several other species previously classified as Spatangus. The clear distinction among different genera was also detected in fossil forms of Spatangus, Propespatagus nov. gen., and Sardospatangus (†) from the European Oligo-Miocene sedimentary rocks of Germany; the Miocene of Ukraine, Italy, and North Africa; the Plio-Pleistocene of Italy; and the Mio-Pliocene of Florida (USA). The new data can help in addressing taxonomic ambiguities within echinoids, as well as in improving species identification, and hence biodiversity assessments in the Mediterranean region.